Versions of trixenic life cycles trematodes from Bithynia (Gastropoda: Proso-branchia Вithyniidae) Palaearctic - E. A. Serbina (Российский паразитологический журнал, 2016)
The data on specific structure of trematodes in mollusks from genius Bithynia are done. It is revealed, that 33 species of trematodes 19 genius of 12 families from Bithynia Palaearctic have 12 versions of trixenic life cycles.